Competition and choice as a guiding principal for housing service reforms: The views of Australian housing professionals. (October 2019) - Jacobs, Keith; Lawson, Julie
Amongst the claims often made to justify contemporary housing reforms in Australia is that extending choice and opening services to competition will lead to improved outcomes for tenants and encourage service agencies to become more efficient. This paper considers the veracity of 'choice' and 'competition' based reforms by drawing on international examples and the views of practitioners working in the Australian housing sector. Situating Australian reforms in an international context it explores why some practitioners have misgivings about policies that seek to advance 'choice' as the guiding principal for housing reform. The key arguments are first: that interventions to extend individual choice are likely to have only limited traction when organizations are struggling to operate with limited resources and second: households on low incomes often struggle to take up the choices that are made available through these service reforms. In the conclusion, it is suggested that the current Australian housing agenda to extend competition and choice is best situated within the wider setting of neoliberal policymaking. Though both concepts might appeal to those advocating consumer rights, their deployment serves to conceal a broader political agenda – to restructure welfare provision in ways that advantage the commercial sector.